Automobile 4s Store Cloud Service System Based on Websocket and React - Huang, Gongyu (fi=Turun yliopisto|en=University of Turku|, 2018)
With the development and penetration of Internet to the mobile internet and internet of things, internet giant and automobile giants have begun a wide range of communication and cooperation. With the relevant vehicle entering into the on-road experiment phase, the automotive industry has become the significant battlefield for the next five to ten years. However, automobile is not an isolated point. The development of it is restricted by many fields. The development of automobile internet is just talk without relative platform to provide important services, one of which is the slow development of automobile 4s store services. Automobile 4s store is an important part of the automotive industry, is not only the irreplaceable link between manufactures and customers, but also the platform which provides automobile related service including vehicle sales, parts, service, information feedback. Traditional car 4s shop profits high, the demand of consumers for cars 4s shop are skyrocketing, but the car 4s shop living conditions is precarious. Currently, the vast majority of 4s automobile stores has become a vassal of automobile manufacturers, no right to speak, and difficult to get rid of dependence on the automobile brand, without its own brand image. It is difficult to recruit professional and technical personnel; the business scope and the factors which may be controlled also very limited. The service most 4s automobile stores provide seriously homogeneous. This article focuses on building cars 4s shop cloud services platform by connecting the consumer, automotive, car 4s shop and car manufacturers, to provide not only consumers with a better car service, but also car 4s shop and car manufacturers of automotive related accumulated data, providing car-related cloud computing platform, in which data analysis can be included. The 4s automobile store cloud services platform while provides a large number of basic data services platform and automotive-related services, leaves a large number of suitable interfaces and expansion for small and medium enterprises to access to the automotive industry. In the actual production process and when the cloud computing platform accumulates enough consumer and